Catalytic Fast Pyrolysis of Biomass Impregnated with Potassium Phosphate in a Hydrogen Atmosphere for the Production of Phenol and Activated Carbon - Lu, Qiang; Zhang, Zhen-xi; Wang, Xin; Guo, Hao-qiang; Cui, Min-shu; Yang, Yong-ping (Frontiers in Chemistry, 2018)
A new technique was proposed to co-produce phenol and activated carbon (AC) from catalytic fast pyrolysis of biomass impregnated with K3PO4 in a hydrogen atmosphere, followed by activation of the pyrolytic solid residues. Lab-scale catalytic fast pyrolysis experiments were performed to quantitatively determine the pyrolytic product distribution, as well as to investigate the effects of several factors on the phenol production, including pyrolysis atmosphere, catalyst type, biomass type, catalytic pyrolysis temperature, and catalyst impregnation content. In addition, the pyrolytic solid residues were activated to prepare ACs with high specific surface areas. The results indicated that phenol could be obtained due to the synergistic effects of K3PO4 and hydrogen atmosphere, with the yield and selectivity reaching 5.3 wt% and 17.8% from catalytic fast pyrolysis of poplar wood with 8 wt% K3PO4 at 550 oC in a hydrogen atmosphere. This technique was adaptable to different woody materials for phenol production. Moreover, gas product generated from the pyrolysis process was feasible to be recycled to provide the hydrogen atmosphere, instead of extra hydrogen supply. In addition, the pyrolytic solid residue was suitable for AC preparation, using CO2 activation method, the specific surface area was as high as 1605 m2/g.